Networks, hacking, and media CITA MS@30 : now and then and tomorrow - Wellman, Barry; Robinson, Laura (Sociologist); Brienza, Casey; Chen, Wenhong; Cotten, Shelia R. (Bingley, U.K. : Emerald Publishing Limited, 2018)
Sponsored by the Communication, Information Technologies, and Media Sociology section of the American Sociological Association (CITAMS), this volume celebrates the section's thirtieth anniversary. Lead editor Barry Wellman joins forces with former and current CITAMS chairs Wenhong Chen, Shelia Cotten, and Laura Robinson, as well as Casey Brienza, founder of the Media Sociology Preconference, to look back at the history of the section, review some of its most important themes, and set the agenda for future discussion.Alongside its sister volume, The "M" in CITAMS@30: Media Sociology, this valuable book shows the impact CITAMS has had, and continues to have, on academic and public discourse. Featuring leading scholars in the fields of sociology of communication, information technologies and media, it reveals how the section had transcended disciplinary boundaries, and demonstrates how it holds the skills to address some of the biggest challenges of our digital age. It is essential reading for all those interested in both the story of CITAMS to date, and the role it will play in the future.
Prelims -- Part I Field analysis: citams past chairs -- Chapter 1 CITAMS @30: learning from the past, plotting a course for the future -- Chapter 2 Section membership and participation in the American sociological review publication process -- Chapter 3 How information technology transforms the methods of sociological research: past and future -- Part II Field analysis: relationships and networks -- Chapter 4 In sync, but apart: temporal symmetry, social synchronicity, and digital connectedness -- Chapter 5 Romantic dissolution and Facebook life: a typology of coping strategies for breakups -- Chapter 6 Long ties as equalizers -- Chapter 7 Black-hat hackers' crisis information processing in the darknet: a case study of cyber underground market shutdowns -- Chapter 8 I click, therefore I am: predicting clicktivist-like actions on candidates' Facebook posts during the 2016 US primary election -- Afterword -- Index.
Includes index.
Print version record
Keywords: Information society -- History; ASA Section on Communication, Information Technologies, and Media Sociology -- History; Social Science -- Media Studies; Communication studies